Analisis Kebutuhan Ruang Terbuka Hijau Dalam Menyerap Emisi Karbondioksida Dari Kegiatan Transportasi Di Kecamatan Sukajadi Kota Pekanbaru - Agustriani, Rina; Reza, Muhammad; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The green open space is one of an effort in order to handling of the increasing the greenhouse gas emission, because green open space has an ability to absorbing the CO2 emission. The purpose of this research is to find out the potential of absorption capacity of CO2 by the pbulic’s green open space and to analyze the level of absoption of CO2 by green open space from transportation activity. The method in this research is calculate the value of CO2 emissions and counting the trees whcih has diameters more than 20 centimeter. The sufficiency of green open space was analyze and then compared the absorbing power of CO2 by trees with number of CO2 emissions that produced. Sukajadi district is produced the CO2 emissions from transportation which is high enough as much as 51.212.465 ton CO2/year. While the ability of CO2 absorption by the public’s green open space in Sukajadi district only 6.456,68 ton CO2/year. The public’s green open space in Sukajadi district thet viewed of absorbing CO2 emissions of transportation is still not enough with percentage is only about 0,0126%.Keywords : Green Open Space, CO2 emissions, and Greenhouse Gas